2019
DOI: 10.1016/j.neuropharm.2019.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of oleoylethanolamide in a primary care sample of depressed patients are increased in those treated with selective serotonin reuptake inhibitor-type antidepressants

Abstract: F., Plasma concentrations of oleoylethanolamide in a primary care sample of depressed patients are increased in those treated with selective serotonin reuptake inhibitor-type antidepressants., Neuropharmacology (2019), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 47 publications
(52 reference statements)
1
28
0
Order By: Relevance
“…Additionally, 30% of grievers were on antidepressants. Thus, the influence of antidepressant use on the circulating eCB findings in grief should be examined in future studies, particularly in light of recent data that antidepressant use alters circulating 2-AG concentrations (Romero-Sanchiz et al, 2019). We did not collect information on early life adversities and a history of losses in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, 30% of grievers were on antidepressants. Thus, the influence of antidepressant use on the circulating eCB findings in grief should be examined in future studies, particularly in light of recent data that antidepressant use alters circulating 2-AG concentrations (Romero-Sanchiz et al, 2019). We did not collect information on early life adversities and a history of losses in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A study of healthy but physically inactive individuals also showed that manipulation of circulating AEA concentrations with an exercise program revealed positive correlations between AEA and mood disturbances (Belitardo de Oliveira et al, 2019). Several studies have found that circulating AEA concentrations are higher in depressed individuals (Hill et al, 2008b;Romero-Sanchiz et al, 2019), although another study found serum AEA concentrations are reduced in major depression (Hill et al, 2009b). On the other hand, the relationship between circulating AEA and symptoms of anxiety in trauma-related conditions is equivocal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, basal serum concentrations of AEA and 2-AG were significantly lower in women with nontreated major depression, and the exposure to a stressful situation significantly increased 2-AG concentrations without modifying AEA (227). However, another study described increased plasma concentrations of both AEA and 2-AG in depressed patients, and the elevation of 2-AG was significantly associated with SSRI antidepressant therapy (228). Interestingly, the antidepressantrelated effects or physical exercise on eCBs levels were also analyzed.…”
Section: Human Studiesmentioning
confidence: 99%
“…Furthermore, observational studies have shown reduced serum levels of AEA and 2-AG in depressed women compared with healthy controls, in one of which a reduction in serum 2-AG progressively decreased over the duration of the disorder ( Hill et al, 2009 , Hill et al, 2008 ). Interestingly, another study found that patients with depression who received selective serotonin reuptake inhibitor (SSRI) treatment had elevated plasma levels of 2-AG compared with those who were not on antidepressant treatment, although this effect was not present for AEA levels ( Romero-Sanchiz et al, 2019 ). The notion of reduced eCB function in depression is particularly interesting in view of the putative anti-inflammatory action of this system (discussed above), as there is a well-established link between increased inflammatory state and depression.…”
Section: Introductionmentioning
confidence: 99%